2016
DOI: 10.3390/nu8060333
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic Acid B Inhibits Aβ Generation by Modulating BACE1 Activity in SH-SY5Y-APPsw Cells

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disease in humans. The accumulation of amyloid-β (Aβ) plays a critical role in the pathogenesis of AD. Previous studies indicated that Salvianolic acid B (SalB) could ameliorate Aβ-induced memory impairment. However, whether SalB could influence the generation of Aβ is unclear. Here, we show that SalB (25, 50, or 100 µM) reduces the generation of Aβ40 and Aβ42 in culture media by decreasing the protein expressions of BACE1 and sAPPβ in SH-SY5Y-APPsw cells. Meanwh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Tang et al and Durairajan et al independently reported that Sal B modulated BACE1 activity in SH-SY5Y-APPsw cells and it decreased Aβ generation in H4-SwedAPP, N2a-SwedAPP, and HEK-BACE1 cells. Many, possibly important, variations can be noticed in these studies: i) Tang et al suggested that BACE1 expression was reduced at 50 µM [53], but Durairajan et al [54] showed that Sal B 8 [55] reported that Sal B shows negligible binding to the catalytic sites using molecular docking methods. Tang et al suggest that Sal B suppresses BACE1 expression.…”
Section: Phenolics and Tannins Having Potential Anti-beta-site Amyloimentioning
confidence: 99%
“…Tang et al and Durairajan et al independently reported that Sal B modulated BACE1 activity in SH-SY5Y-APPsw cells and it decreased Aβ generation in H4-SwedAPP, N2a-SwedAPP, and HEK-BACE1 cells. Many, possibly important, variations can be noticed in these studies: i) Tang et al suggested that BACE1 expression was reduced at 50 µM [53], but Durairajan et al [54] showed that Sal B 8 [55] reported that Sal B shows negligible binding to the catalytic sites using molecular docking methods. Tang et al suggest that Sal B suppresses BACE1 expression.…”
Section: Phenolics and Tannins Having Potential Anti-beta-site Amyloimentioning
confidence: 99%
“…A summary of in vitro effects that attributes to the potential therapeutic effects of salvianolic acid derivatives are shown in Table 1 [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. By assessing the β-secretase (β-site amyloid precursor protein (APP) cleaving enzyme or BACE1) and γ-secretase inhibitory activity, a selective effect against BACE1 was demonstrated for SA-B [ 32 ].…”
Section: Salvianolic Acids and Dementiamentioning
confidence: 99%
“…Moreover, the direct interaction of the compound with the catalytic center of the enzyme has been confirmed by docking experiments [ 32 ]. In SH-SY5Y-APPsw cells, the Aβ40 and Aβ42 levels in culture media has been shown to be suppressed by SA-B [ 33 ]. While the protein expression of APP was not affected by SA-B, it has been shown to increase the protein level expressions of “a disintegrin and metalloproteinase domain-containing protein 10” (ADAM10) and secreted APP-α (sAPPα) concomitantly with the decreased protein expressions of BACE1 and sAPPβ [ 33 ].…”
Section: Salvianolic Acids and Dementiamentioning
confidence: 99%
See 2 more Smart Citations